Second method of Lyapunov for stability of linear impulsive differential-difference equations with variable impulsive perturbations. (1998) - Bainov, D. D.; Stamova, I. M.; Vatsala, A. S.
Abstract : The present work is devoted to the study of stability of the zero solution to linear impulsive differential-difference equations with variable impulsive perturbations. With the aid of piecewise continuous auxiliary functions, which are generalizations of the classical Lyapunov's functions, sufficient conditions are found for the uniform stability and uniform asymptotical stability of the zero solution to equations under consideration.